Characterization and antimicrobial activity of N-methyl-2-pyrrolidone- loaded ethylene oxide-propylene oxide block copolymer thermosensitive gel - Phaechamud T. (2017)
The purpose of this study is to investigate the effects of N-methyl-2-pyrrolidone on the thermosensitive properties of aqueous ethylene oxide-propylene oxide block copolymer (Lutrol ® F127)] system. Due to the aqueous solubility enhancement and biocompatibility, N-methyl-2-pyrrolidone is an interesting solubilizer for the poorly water soluble drugs to be incorporated in the Lutrol ® F127 system. Effect of N-methyl-2-pyrrolidone on physicochemical properties of Lutrol ® F127 system was investigated using appearance, pH, gelation, gel melting temperature and rheology. The antimicrobial activity of the thermosensitive N-methyl-2-pyrrolidone gel was also tested. Lower N-methyl-2-pyrrolidone amount (8804:30%w/w) could shift the sol-gel transition to a lower temperature but the gel-sol transition was shifted to a higher temperature. Higher N-methyl-2-pyrrolidone (≥40%w/w) could shift both sol-gel and gel-sol transitions of the system to a lower temperature. The amount of N-methyl-2-pyrrolidone > 60% w/w could reverse the phase of the Lutrol ® F127 system to non-newtonian flow at 4° and Newtonian flow at high temperature. Aqueous Lutrol ® F127 system containing N-methyl-2-pyrrolidone exhibited antimicrobial activities against Staphylococcus aureus, Escherichia coli and Candida albicans with the N-methyl-2-pyrrolidone in a dose-dependent manner.